2021
DOI: 10.2174/1573399816666201103143225
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Medicines for Diabetes Management and its Secondary Complications

Abstract: : Diabetic Mellitus (DM) is a metabolic disorder that has attracted worldwide concern. DM is caused due to lack of insulin or ineffective production of insulin in the pancreas. A total of 463 million people have diabetes mellitus in 2019 and it was predictedto raise upto 578 million by 2030 and 700 million by 2045. High blood sugar gives rise to many complications like diabetic retinopathy, diabetic nephropathy, atherosclerosis, hypercoagulability, cardiovascular disease, coronary heart disease, abdominal obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 114 publications
0
69
0
2
Order By: Relevance
“…Although mild α-amylase inhibition is beneficial for blunting glucose spikes, excessive inhibition may induce starch indigestion and abnormal bacterial fermentation, causing abdominal pain, bloating or cramping [22]. Acarbose can induce these undesirable effects due to its potent inhibition of human and mammalian pancreatic α-amylase [11].…”
Section: Comparing Flavonoids To Acarbosementioning
confidence: 99%
See 1 more Smart Citation
“…Although mild α-amylase inhibition is beneficial for blunting glucose spikes, excessive inhibition may induce starch indigestion and abnormal bacterial fermentation, causing abdominal pain, bloating or cramping [22]. Acarbose can induce these undesirable effects due to its potent inhibition of human and mammalian pancreatic α-amylase [11].…”
Section: Comparing Flavonoids To Acarbosementioning
confidence: 99%
“…Some flavonols excreted in urine can be used as biomarkers of flavonol intake and are significantly associated with a lower T2D risk [21]. Many flavonoids extracted from plants inhibit α-amylase and α-glucosidases activities in vitro and improved postprandial glycaemia in diabetic animal models and limited human studies [22,23]. Very few studies have reported on the inhibition of isomaltase, however.…”
Section: Introductionmentioning
confidence: 99%
“…As of 2019, the number of people with DM has reached a total of 463 million. It is estimated that the number will reach 578 million by the year of 2030 and 700 million by 2045 [1]. Driven by the lack of insulin or ineffective production of insulin in the pancreas, high blood sugar gives rise to many life-threatening diabetic complications and makes DM a leading cause of cardiovascular morbidity and mortality, renal failure, amputations, and blindness [2].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of phytoconstituents such as terpenoids, flavonoids and coumarins are counted for the anti-diabetic nature of the medicinal plants. Picnagenol, acarbose, miglitol, and voglibose are some of the marketed anti-diabetic drugs of natural origin [4]. Cissampelos pareira (C.pareira) is a climbing herb distributed in tropical and subtropical war regions of Africa, Asia, and America [5].…”
Section: Introductionmentioning
confidence: 99%